Mechanical behaviour׳s evolution of a PLA-b-PEG-b-PLA triblock copolymer during hydrolytic degradation. (July 2016) - Breche, Q.; Chagnon, G.; Machado, G.; Girard, E.; Nottelet, B.; Garric, X.; Favier, D.
Abstract: PLA- b -PEG- b -PLA is a biodegradable triblock copolymer that presents both the mechanical properties of PLA and the hydrophilicity of PEG. In this paper, physical and mechanical properties of PLA- b -PEG- b -PLA are studied during in vitro degradation. The degradation process leads to a mass loss, a decrease of number average molecular weight and an increase of dispersity index. Mechanical experiments are made in a specific experimental set-up designed to create an environment close to in vivo conditions. The viscoelastic behaviour of the material is studied during the degradation. Finally, the mechanical behaviour is modelled with a linear viscoelastic model. A degradation variable is defined and included in the model to describe the hydrolytic degradation. This variable is linked to physical parameters of the macromolecular polymer network. The model allows us to describe weak deformations but become less accurate for larger deformations. The abilities and limits of the model are discussed.